Talent map: how demographic rate, human development index and birthdate can be decisive for the identification and development of soccer players in Brazil - Teoldo, I.; Cardoso, F. (Science and Medicine in Football, 2021)
Aim: The aim of this paper is to verify how cities` demographic rates and Human Development Index (HDI), as well as the birthdate of Brazilian elite soccer players influenced their identification and development. Methods: The sample was comprised of 5,359 players from the Brazilian Serie A Soccer Championship between 2003 and 2019. Players` birthdate and birthplace data were collected, as well as the HDI from their hometowns. Descriptive statistics, chi-square, Pearson correlation and linear regression tests were performed. Results:Results indicated that players born in the first semester of the year, in cities with a demographic rate of up to 100,000 inhabitants and HDI above 0.501, are more likely to play at the highest level (Serie A) of Brazilian soccer. Correlations were observed between birth quartile and HDI (r = -.059; se = 0.04; p < 0.001), birth quartile and demographic rates (r = -063, se = 0.03; p < 0.001), and between HDI and demographic rates (r = 0.458; se = 0.02; p < 0.001). The linear regression method yielded a valid model that included all three variables in this study (F(2) = 9.512; p < 0.001). Conclusion: Based on these findings, it is possible to conclude that birthdate, demographic rate and HDI are important factors in the identification and development of soccer players in Brazil.